Anti-cancer effect of a novel photodynamic therapy using glucose-linked chlorin e6 conjugated trastuzumab for HER2-positive gastrointestinal cancers - Makiko Sasaki; Mamoru Tanaka; Akihiro Nomoto; Ryusei Yamasaki; Tomokazu Yoshimura; Shigenobu Yano; Yasunari Sasaki; Yuki Kojima; Taketo Suzuki; Hirotada Nishie; Keiji Ozeki; Takaya Shimura; et al. (PLoS ONE, 2026)
Photodynamic therapy (PDT) is an anti-cancer therapy that employs a photosensitizer (PS) and an optimal wavelength of light, causing a photochemical reaction that releases reactive oxygen species, thereby inducing cancer cell death via oxidative stress. Because light irradiation is limited to the tumor site, PDT has minimal adverse effects. The cancer cell selectivity of the PS is important for reducing damage to the normal mucosa caused by scattered light. Antibody-drug conjugates (ADC) are novel anti-cancer therapies that combine a monoclonal tumor-surface-receptor-targeting antibody with a drug bonded through chemical linkers. ADCs enable the targeted delivery of a variety of drugs to cancer cells while minimizing their delivery to healthy tissues. One such tumor surface receptor is the human epidermal growth factor receptor 2 (HER2), which is of interest in the treatment of many cancers, including gastrointestinal cancer. To improve tumor selectivity and minimize damage to the mucosa surrounding the tumor in PDT, we established a novel PS glucose-linked chlorin e6-conjugated trastuzumab (G-Ce6-trastuzumab) that is conjugated to existing PS glucose-linked chlorin e6 (G-Ce6) and evaluated its anti-cancer effect compared to G-Ce6. The effect of PDT was evaluated using HER2-high-expression cells NCI-N87 and HER2-low-expression cells MKN-45. G-Ce6-trastuzumab is internalized by the intracellular organelles in cancer cells. Evaluation of cell death using the WST-8 assay also demonstrated a significantly higher cytotoxic effect of G-Ce6-trastuzumab in HER2-high-expression cells compared with conventional PS G-Ce6. Thereby, G-Ce6-trastuzumab may be an excellent novel PS for PDT because of its strong selectivity for HER2-high-expression cells.